POLITISASI KONSTITUSI PIUTANG NEGARA DI INDONESIA - Agus Pandoman (Universitas Slamet Riyadi, 2018)
One example of the problems in the state's claim is BLBI extended by Bank Indonesia to the national banking system, which has become the state's claim, but not resolved through PUPN, but further right to claim the government handed over to IBRA established by Presidential Decree No. 27 of 1998 . Since handed over to the government the right to collect BI, BI ended authority to withdraw BLBI of the receiving bank, resolved through non-litigation and mechanisms and the solution was not to use repressive laws. Receivables BLBI state is a case of default the unusually large number (extraordinary default), but penyelesaianya by IBRA implemented with the exclusion of the legal principles of the settlement of accounts receivable against the debtor country BLBI receiver, so in this case the journey is also a cost for settling disputes outstanding a big. This paper would like to see how the practice of politicizing the constitution that happens particularly with respect to issues of State receivables.